2021
DOI: 10.1111/den.14193
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound versus magnetic resonance cholangiopancreatography for the diagnosis of computed tomography‐negative common bile duct stone: Prospective randomized controlled trial

Abstract: Objectives For suspected common bile duct stone (CBDS) missed on computed tomography (CT), there is no clear evidence on whether endoscopic ultrasound (EUS) or magnetic resonance cholangiopancreatography (MRCP) is the better diagnostic tool. We aimed to compare the diagnostic accuracy of EUS and MRCP for cases of missed CBDS on CT. Methods Patients suspected of having CBDS were enrolled and randomly allocated to the EUS or MRCP group. Upon the initial examination, those having CBDS or sludge formation underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
(35 reference statements)
0
8
1
Order By: Relevance
“…A study that was conducted in the Japan showed inconsistent results with positive predictive value (50.0%) and negative predictive value (73.30%). 14 The difference in this current study results in comparison to the results of international studies could be due to various reasons such as variation in the expertise level of operators and errors in documentation. Furthermore, a study has indicated that MRCP sensitivity, specificity, and accuracy goes up when stones size gets larger and higher contrast resolution are used in diagnosing the choledocholithiasis.…”
Section: Discussioncontrasting
confidence: 69%
“…A study that was conducted in the Japan showed inconsistent results with positive predictive value (50.0%) and negative predictive value (73.30%). 14 The difference in this current study results in comparison to the results of international studies could be due to various reasons such as variation in the expertise level of operators and errors in documentation. Furthermore, a study has indicated that MRCP sensitivity, specificity, and accuracy goes up when stones size gets larger and higher contrast resolution are used in diagnosing the choledocholithiasis.…”
Section: Discussioncontrasting
confidence: 69%
“…One prospective RCT [3] showed no significant superiority of EUS over MRCP in diagnosing biliary disease in patients with intermediate risk of choledocholithiasis (i.e., patients with dilated CBD on ultrasound of the abdomen and/or altered LFTs). On the other hand, both a Japanese RCT conducted in patients with suspected common bile duct stones but negative computed tomography [4] and a recently published meta-analysis showed higher sensitivity and accuracy of EUS over MRCP in detecting choledocholithiasis [5]. In one prospective study in patients with idiopathic acute pancreatitis [6], EUS found more biliary stones, whereas MRCP identified pancreatic duct abnormalities with higher sensitivity.…”
Section: Eus For the Diagnosis Of Acute Pancreatitismentioning
confidence: 99%
“…[13] Early surgical options could be considered for patients who are appropriate candidates without risks of serious complications such as cholangitis or organ dysfunction. [39] Certain groups of patients previously had high rates of ERCP such as those with high suspicion of type III SOD and were later found to have no benefit from empiric sphincterotomy. [26,43] The SOD is a concentric muscle, that responds to hormonal input, found in the pre-ampullary portion of the pancreatic and bile ducts.…”
Section: Patient Selectionmentioning
confidence: 99%